Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Nilai-Nilai Karakter Dasa Darma Pramuka pada Pembelajaran PPKn Kelas V SDN 72 Bengkulu Tengah - Hendriwati, Hendriwati; Djuwita, Puspa; Hambali, Daimun (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2021)
Abstract This research is motivated by a decrease in the character values of students and the absence of a LKPD that contains the character values of Dasa Darma Pramuka at SDN 72 Bengkulu Tengah. This affects the achievement of learning objectives, namely forming students with character. This study aims to determine the validity and practicality of LKPD based on the values of Dasa Darma Pramuka. This research is a development research using the 4- D model which consists of four stages, namely define, design, develop and disseminate. This research was only conducted until the develop stage, namely the validity test and practicality test. The instrument used was a validity test questionnaire and a practicality test questionnaire. The validity test was carried out by 6 validators, namely 2 material experts, 2 linguists and 2 graphic experts. The practicality test was carried out on 19 students of SDN 72 Bengkulu Tengah. Data from the validity and practicality test results were analyzed by using percentage techniques and processed descriptively. The results of the LKPD validity test based on the values of Dasa Darma by the validator in terms of aspects of the front page, table of contents, study instructions, material feasibility, language presentation, and graphic feasibility, material eligibility was obtained 0.81 with proper criteria, language eligibility results 0, 75 with very feasible criteria and a graphical feasibility result of 0.81. The practicality test results of the LKPD based on the values of the Dasa Darma Pramuka, obtained a value of 80.69 by the teacher and 80.95 by students with practical criteria. Based on the results of the study it can be concluded that the use of LKPD values of Dasa Darma Pramuka SDN 72 Bengkulu Tengah in grade V is very feasible and very practical. Keywords : Dasa Darma, Character, student worksheet